A high-performance, highly bendable quasi-solid-state zinc–organic battery enabled by intelligent proton-self-buffering copolymer cathodes. Issue 29 (15th July 2019) - Li, Ping; Fang, Zhengsong; Zhang, You; Mo, Chunshao; Hu, Xuanhe; Jian, Junhua; Wang, Shuangyin; Yu, Dingshan
Abstract : A specially designed poly(aniline- co -azure C) (PANAC) copolymer cathode harnesses intelligent proton-self-buffering capability and fast electron/ion transport in a highly bendable, quasi-solid-state Zn–PANAC battery. Abstract : Herein, we report the first prototype of a highly bendable, quasi-solid-state Zn–poly(aniline- co -azure C) (PANAC) battery. The conformal assembly of the PANAC copolymer onto a porous carbon-sheathed carbon cloth was explored as a cathode, rendering the rich protonated nitrogen at a charged state and unique "proton-self-supplier" to drastically boost the polymer electroactivity in near-neutral aqueous electrolytes while enabling rapid electron/ion transport. This strategy harnesses the smart "proton-self-regulation" capability of a phenothiazine derivative in PANAC to surmount a long-standing conflict that the high electroactivity of the traditional polyaniline cathode demands a highly acidic environment, which is incompatible with Zn anodes. Thus, the aqueous Zn–PANAC cell delivers an impressive capacity and energy density of 306.3 mA h g −1 and 352.3 W h kg −1, respectively, – the highest values among the current zinc–polymer cells. The quasi-solid-state cell also yields a high capacity and energy density of 241.4 mA h g −1 and 289.3 W h kg −1, respectively, with a long lifespan (over 1000 cycles), and functions well when being bent, twisted, punctured and sewn.